Obraz pasterzy w staropolskich kolędach i pastorałkach (na materiale tzw. „Kantyczek karmelitańskich” z XVII i XVIII wieku) - Borejszo, Maria (Slavia Occidentalis, 2012)
The image of shepherds in old Polish Christmas carols and pastoral Christmas carols (based on the material provided by the so-called Carmelite Canticles “Kantyczki karmelitańskie” from the 17th and the 18th centuries) Summary The article discusses the images of shepherds, that have come to be identified with Christmas, as they were created in Christmas carol songs written by Polish authors through the seventeenth and the eighteenth centuries. The study covers 358 songs included in the so-called “Kantyczki karmelitańskie” (Carmelitan Canticles) compiled and written down in the eighteenth century (presumably from the 1720s to the end of the century) for the use of the Cracow-based Carmelite nuns. In 1980, the collection of songs was published by Barbara Krzyżaniak (see Kantyczki karmelitańskie. Rękopis z XVIII wieku, przygotowała do wydania B. Krzyżaniak, Kraków 1980, 419). A thorough analysis of the collection has made it possible to identify that a large portion of the Christmas carols that introduce the pastoral thread make up for the bulk of the manuscript under scrutiny (about 46 per cent of the texts). These are original songs, deeply embedded in Old Polish social and natural reality (with mainly pastoral and rustic setting), and thus easily reaching a wide audience of the time. The image of shepherds reconstructed on the basis of the works in the collection includes such elements as: 1) Christian names, surnames (patronymics), and nicknames of shepherds (in all, more than 140 anthroponyms, included in the appendix); 2) characteristic physical and psychological features attributed to particular members of the community of shepherds; 3) the set of social rules governing the relations within the group; 4) particular distinctive and characteristic elements of represented world in which the community operated (e.g. shepherd’s attires, home utensils and equipment to be used for agricultural production, food and dairy products, farm animals and musical instruments). The author claims that the informative nature of the texts clearly indicates that the image of shepherds preserved in Christmas carols had been succumbed to a far-reaching Polonisation process. The settings for the Christmas carol songs were thus purposefully and consistently embedded in Polish local and authentic reality, which undoubtedly gave them mass appeal to people across a wide spectrum of social sectors. Keywords: literature, the Enlightenment, religious lyric poetry, song, Christmas carol, pastoral Christmas carol, religion, Christmas